НЕФІНАНСОВА МОТИВАЦІЯ ПРАЦІВНИКІВ ПІДПРИЄМСТВ В УМОВАХ КРИЗИ - Ясінська, Й. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
The crisis amplifies the imperfections of management systems, including the area of human resources management in organizations. Despite the bad market situation, a company in trouble can not afford to lose key employees or decrease their motivation. Whether the company finds a way out of the crisis or disappears from the market largely depends on the motivation of its employees. The author presents the results of her own research conducted from September 2015 to March 2016 on crisis situations in enterprises. The study covered a group of 70 managers of Lubuskie companies of different sizes. The categorical and questionnaire interview method was used. The research tool was selfprepared questionnaire interview.